Measuring the impact of olive pomace enriched biscuits on the gut microbiota and its metabolic activity in mildly hypercholesterolaemic subjects - Conterno, Lorenza; Martinelli, Francesca; Tamburini, Matteo; Fava, Francesca; Mancini, Andrea; Sordo, Maddalena; Pindo, Massimo; Martens, Stefan; Masuero, Domenico; Vrhovsek, Urska; Dal Lago, Claudia; Ferrario, Gabriele; et al. (European journal of nutrition, 2019)
Purpose Olive pomace is a major waste product of olive oil production but remains rich in polyphenols and fibres. We measured the potential of an olive pomace-enriched biscuit formulation delivering 17.1 ± 4.01 mg/100 g of hydroxytyrosol and its derivatives, to modulate the composition and metabolic activity of the human gut microbiota. Methods In a double-blind, controlled parallel dietary intervention 62 otherwise healthy hypercholesterolemic (total plasma cholesterol 180–240 mg/dl) subjects were randomly assigned to eat 90 g of olive pomace-enriched biscuit (olive-enriched product, OEP) or an isoenergetic control (CTRL) for 8 weeks. Fasted blood samples, 24-h urine and faecal samples were collected before and after dietary intervention for measurement of microbiota, metabolites and clinical parameters. Results Consumption of OEP biscuits did not impact on the diversity of the faecal microbiota and there was no statistically significant effect on CVD markers. A trend towards reduced oxidized LDL cholesterol following OEP ingestion was observed. At the genus level lactobacilli and Ruminococcus were reduced in OEP compared to CTRL biscuits. A trend towards increased bifidobacteria abundance was observed after OEP ingestion in 16S rRNA profiles, by fluorescent in situ hybridization and by qPCR. Targeted LC–MS revealed significant increases phenolic acid concentrations in 24-h urine following OEP ingestion and 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid, derivatives of hydroxytyrosol, were elevated in blood. A sex effect was apparent in urine small phenolic acid concentrations, and this sex effect was mirrored by statistically significant differences in relative abundances of faecal bacteria between men and women. Conclusion Ingestion of OEP biscuits led to a significant increase in the metabolic output of the gut microbiota with an apparent sex effect possibly linked to differences in microbiota makeup. Increased levels of homovanillic acid and DOPAC, thought to be involved in reducing oxidative LDL cholesterol, were observed upon OEP ingestion. However, OEP did not induce statistically significant changes in either ox-LDL or urinary isoprostane in this study.